2021
DOI: 10.3389/fpsyg.2021.762213
|View full text |Cite
|
Sign up to set email alerts
|

Distance Learning During the First Lockdown: Impact on the Family and Its Effect on Students' Engagement

Abstract: This contribute investigates how Emergency Remote Education (ERE) impacted families during the spring 2020 Covid-19 lockdown, and in particular, the extent to which the impact of ERE on families, measured in terms of space and equipment sharing, moderates the effect of student and family characteristics on students' engagement. The study derived from the administration of an online survey to 19,527 families with children attending schools, from nursery to upper secondary grade. The total number of student reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…The greater motivation with school activities at home was associated by mothers and fathers with the development of collaborative activities proposed by the school; however, said motivation was negatively mediated when there was a greater need to share spaces at home and technological tools [24] .…”
Section: Emergency Distance Learningmentioning
confidence: 98%
See 2 more Smart Citations
“…The greater motivation with school activities at home was associated by mothers and fathers with the development of collaborative activities proposed by the school; however, said motivation was negatively mediated when there was a greater need to share spaces at home and technological tools [24] .…”
Section: Emergency Distance Learningmentioning
confidence: 98%
“…Lower performance was observed in students, who generally came from lower-income countries and families [42] . Factors studied that would be associated with said performance correspond to: monetary limitations of the family in access to technological materials [24] , sharing devices with other members of the family [43] , within the group of adolescents identified living in homes that are too full of other people [44] .…”
Section: Family Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Support for the intuitive hypothesis that more in-home distraction can make learning over video-chat more challenging comes from other recent research on children's learning during pandemic-related remote learning situations. When measuring the factors impacting the success of remote learning for school children, Chifari et al (2021) found a latent variable, "impact on the family, " that affected engagement levels. During the first few weeks of lockdown, children's engagement levels were lower if they needed to share a learning space, as well as technological resources, with their family.…”
Section: Why Is Fast Mapping From Smsr Challenging?mentioning
confidence: 99%
“…It is widely recognized that this situation had a significant impact on students’ learning and well-being and that prompted an unexpectedly massive use of technologies to ensure continuity of education via remote lessons ( Organisation for Economic Co-operation and Development [OECD], 2021a , 2021b ). The need to shift from a traditional face-to-face educational paradigm to emergency remote teaching and learning (ERTL) represented a challenge for educational systems, schools, teachers, and families ( Chifari et al, 2021 ), and also affected School in Hospital (SiHo) services – the services that provide educational continuity for hospitalized students – in countries where these are available ( Benigno et al, 2020 ; Caggiano et al, 2021 ; Gajda et al, 2021 ).…”
mentioning
confidence: 99%